Diferentes potências da terapia a laser de baixa intensidade no reparo tendíneo, em ratos - Neves, Marco Aurelio Invaldi [UNIFESP] (2009)
Introduction: Calcaneous tendon is one of the most damaged tendons, and its healing may last from weeks to months to be completed. In the search after speeding tendon repair, low intensity laser therapy has shown favorable effect. Objective: To assess the effect of 40, 60, 80 and 100mW powers of low level laser on the process of tissue repair in partial lesion calcaneous tendon in rats. Methods: The was used 830-nm GaAlAs diode laser operating at output powers of 40, 60, 80 and 100 mW and energy density of 30 J/cm2 on the repair of partial calcaneal tendon ruptures in rats. A partial tendon rupture was induced in all animals, which were treated with laser irradiation for 5 consecutive days. Six days after injury, the injured tendons were removed and examined by polarized light microscopy. Results: Collagen fiber organization was evaluated by birefringence measurements, and collagen content was determined by picrosirius red staining. It was observed that the higher the output power (60-100 mW) the greater was the amount of type III collagen (P < 0.01). The amount of type I collagen was significantly greater (P = 0.05) in the 80-mW group than in the control group (sham stimulation). A non-statistically significant improvement in the realignment of collagen fibers was observed in the irradiated groups. Conclusion: Low-level laser therapy resulted in significantly greater amounts of type III collagen (output powers of 60 mW or more) and type I collagen (output power of 80 mW), however, no significant differences between groups were found in the realignment of collagen fibers.